Improved Adaptive LSB Steganography Based on Chaos and Genetic Algorithm. (20th June 2010) - Yu Yu, Lifang Lifang; Zhao Zhao, Yao Yao; Ni Ni, Rongrong Rongrong; Li Li, Ting Ting
Abstract : We propose a novel steganographic method in JPEG images with high performance. Firstly, we propose improved adaptive LSB steganography, which can achieve high capacity while preserving the first-order statistics. Secondly, in order to minimize visual degradation of the stego image, we shuffle bits-order of the message based on chaos whose parameters are selected by the genetic algorithm. Shuffling message's bits-order provides us with a new way to improve the performance of steganography. Experimental results show that our method outperforms classical steganographic methods in image quality, while preserving characteristics of histogram and providing high capacity.